Process Development of Halaven®: Synthesis of the C1–C13 Fragment from d-(–)-Gulono-1,4-lactone - Chase, Charles E.; Fang, Francis G.; Lewis, Bryan M.; Wilkie, Gordon D.; Schnaderbeck, Matthew J.; Zhu, Xiaojie (Synlett, 2013)
A 12-step kilogram-scale synthesis of the C1–C13 fragment, common to halichondrin B and the totally synthetic analogue Halaven® (E7389, INN eribulin mesylate), is described. The synthesis features four crystalline intermediates which facilitates throughput, and enhances quality control of all stereogenic centers in the title compound.
Keywords: carbohydrates; chiral pool; drugs; glycosylation; stereoselective synthesis